Pengaruh Cash Conversion Cycle terhadap Profitabilitas Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010-2017 - Megawati, Megawati; Mulyanto, Sigit (Universitas Darwan Ali, 2020)
This study aims to determine the effect of the cash conversion cycle on the profitability of manufacturing companies listed on the Indonesian Stock Exchange (BEI). The sampling technique used is purposive sampling. The sample used in this research is 83 companies consisting of 23 companies from the consumer goods sector, 36 from primary industry and chemicals, and 24 from the miscellaneous industry. The dependent variable in this study is profitability proxied to return on assets (ROA). The independent variable is the cash conversion cycle and there are three control variables in this study, namely debt, growth, and size. This research was conducted using multiple linear regression. The result of this research shows that the cash conversion cycle did not affect profitability in the manufacturing sector which is listed on the Indonesian Stock Exchange (BEI).